Efisiensi Produksi Usahatani Padi Sawah Kelompok Subak dan Non Subak di Kabupaten Kolaka - Muhammad Obi Kasmin; Nyoman Darsana (AGRIMOR, 2019)
"The use of local wisdom in the management of agriculture is a solution to improve the efficiency of agriculture. Subak is a form of local wisdom in the management of wetland rice cultivation, which until now is still used by some people from Bali Island in the overseas region. The community applying the subak system believes that the management of its operations is more efficient through the implementation of the subak system. This study aims to determine the income of subak and non subak groups and the relationship between socio-cultural subak and income from wetland rice cultivation. Data collection is done by the observation method, interviews and bibliographic studies on the sample / respondent of the study. The research respondents were 60, determined by design and randomly. The analysis used is a descriptive statistical analysis. The results showed that the income of farmers in the subak group was higher than that of non-subak farmers with an average income of IDR 12,672,686.67 for the subak group and IDR10,198,529.41 for the non-subak group. There is no structured relationship between socio-cultural income and the total income of each responding farmer, whether subak or non-subak, but if the sociocultural score is high, the income obtained by farmers is also high.